2017
DOI: 10.1002/hep.29144
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA 181b‐3p and its target importin α5 regulate toll‐like receptor 4 signaling in Kupffer cells and liver injury in mice in response to ethanol

Abstract: Increased inflammatory signaling by Kupffer cells contributes to alcoholic liver disease (ALD). Here we investigated the impact of small-specific sized hyaluronic acid of ~35kD (HA35) on ethanol-induced sensitization of Kupffer cells, as well as ethanol-induced liver injury in mice. Un-biased analysis of microRNA (miRNA) expression in Kupffer cells identified miRNAs regulated by both ethanol and HA35. TLR4-mediated signaling was assessed in primary cultures of Kupffer cells from ethanol- and pair-fed rats afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
64
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 36 publications
0
64
0
Order By: Relevance
“…miR‐21 also has a positive correlation with activation of LPS signaling in response to ethanol (Alam & O'Neill, ). Decreased miR‐181b‐3p in liver and macrophages isolated from alcohol‐fed mice promotes expression of importin α5, a protein associated with translocation of p65 to the nucleus, and enhances sensitivity of TLR4 signaling (Saikia et al, ). In addition to TLR4, TLR7/let‐7 contributes to EtOH‐induced hepatic inflammation in AH (Massey et al, ).…”
Section: Roles Of Mi‐rnas In Aldmentioning
confidence: 99%
“…miR‐21 also has a positive correlation with activation of LPS signaling in response to ethanol (Alam & O'Neill, ). Decreased miR‐181b‐3p in liver and macrophages isolated from alcohol‐fed mice promotes expression of importin α5, a protein associated with translocation of p65 to the nucleus, and enhances sensitivity of TLR4 signaling (Saikia et al, ). In addition to TLR4, TLR7/let‐7 contributes to EtOH‐induced hepatic inflammation in AH (Massey et al, ).…”
Section: Roles Of Mi‐rnas In Aldmentioning
confidence: 99%
“…Similarly, miRNA-217 is found to be increased in ethanol-treated macrophages/KCs and leads to inflammatory activity by disrupting Siruin1-lipin-1 signaling (Yin et al, 2015). More recently, Dr. Nagy’s group demonstrated that miR181b-3p in KCs plays an important role in the control of liver injury and inflammation in ethanol-fed mice via the regulation of importin α5 and sensitivity of TLR4-mediated signaling (Saikia et al, 2017). A small specific-sized hyaluronic acid 35 (HA35) treatment can normalize the dysregulated miR181b-3p in KCs and ameliorate ALD in mice, suggesting that HA35, miR-181b-3p, or combination may have therapeutic potential for the treatment of ALD (He & Gao, 2017; Saikia et al, 2017).…”
Section: The Role Of Microrna In Inflammation Of Aldmentioning
confidence: 99%
“…Many potential targets against inflammation have been identified in preclinical studies of ALD, but none of them have been approved to be effective in the clinic for the treatment of patients with ALD yet. In this issue of Hepatology , Saikia et al add two more new targets including a small specific‐sized hyaluronic acid (HA) 35 (HA35) and microRNA (miRNA) 181b‐3p that may have therapeutic potential for the treatment of ALD. By screening a series of small specific‐sized HA fragments including HA7, HA12, HA59, HA35, and HA74 for their immunoregulatory effects on Kupffer cells from ethanol‐fed rats, the authors identified that only small specific‐sized HA of ∼35 kDa (HA35) completely normalized the overactivated Kupffer cells from ethanol‐fed rats in vitro and in vivo .…”
mentioning
confidence: 99%
“…Dependent on the size and matrix structure of the HA molecules and interaction with various types of HA binding proteins and receptors, HA can act either as an anti‐inflammatory mediator or as a proinflammatory factor in response to tissue damage . The study by Saikia et al clearly demonstrated that HA35, but not several other small‐sized HAs they tested, acts as a potent anti‐inflammatory mediator to ameliorate ethanol‐induced overactivation of Kupffer cells in vivo and in vitro . Further mechanistic studies demonstrated that the inhibitory effect of HA35 on hepatic inflammation is mediated by restoring the miRNA‐181b‐3p expression in Kupffer cells that is down‐regulated by ethanol.…”
mentioning
confidence: 99%
See 1 more Smart Citation